EFFICIENCY OF USING MODERN VENTILATION SYSTEMS IN RESIDENTIAL PREMISES - BILYK, ARTEM; GYMENUK, ROMAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article provides a comprehensive analysis of the effectiveness of modern ventilation systems in residential premises. The relevance of the study is due to increased requirements for air quality, energy conservation and comfort in urban environments and energy shortages. The main types of ventilation systems are considered - natural, mechanical, supply and exhaust with heat recovery, as well as intelligent automated systems that respond to changes in microclimate parameters in real time. Special attention is paid to the impact of ventilation on critical indoor air quality parameters, including humidity regulation, temperature stabilization, carbon dioxide (CO₂) concentration control, and the effective removal of harmful airborne pollutants such as volatile organic compounds (VOCs), dust particles, and microbial contaminants. The study highlights the role of properly designed ventilation systems in preventing the accumulation of moisture, which can lead to mold growth and structural damage, as well as in reducing the risk of respiratory diseases and allergic reactions among residents. The article presents a detailed methodology for evaluating the energy efficiency of different types of ventilation systems. This includes a comprehensive assessment of capital investment for system installation, ongoing maintenance costs, electricity consumption for air movement and control, and potential energy savings achieved through heat recovery. The results of the study confirm that the implementation of modern energy-efficient ventilation solutions in residential construction contributes to improving the quality of life, reducing energy costs, and protecting the environment. The findings may be useful for professionals in the fields of engineering design, construction, and energy auditing.